Preparation and characterization of amorphous manganese sulfide thin films by SILAR method - Pathan, H. M.; Kale, S. S.; Lokhande, C. D.; Han, Sung-Hwan; Joo, Oh-Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Manganese sulfide thin films were deposited by a simple and inexpensive successive ionic layer adsorption and reaction (SILAR) method using manganese acetate as a manganese and sodium sulfide as sulfide ion sources, respectively. Manganese sulfide films were characterized for their structural, surface morphological and optical properties by means of X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis and optical absorption measurement techniques. The as-deposited film on glass substrate was amorphous. The optical band gap of the film was found to be thickness dependent. As thickness increases optical band gap was found to be increase. The water angle contact was found to be 34 degrees, suggesting hydrophilic nature of manganese sulfide thin films. The presence of Mn and S in thin film was confirmed by energy dispersive X-ray analysis. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: IONIC-LAYER ADSORPTION; HYDROTHERMAL SYNTHESIS; MNS; GROWTH; DEPOSITION; PHOTOLUMINESCENCE; ZNS